Nationwide evaluation of the advanced clinical practitioner role in England: a cross-sectional survey. Issue 1 (5th January 2022) - Fothergill, Lauren Jade; Al-Oraibi, Amani; Houdmont, Jonathan; Conway, Joy; Evans, Catrin; Timmons, Stephen; Pearce, Ruth; Blake, Holly
Abstract : Background and study objective: In response to growing pressures on healthcare systems, the advanced clinical practice (ACP) role has been implemented widely in the UK and internationally. In England, ACP is a level of practice applicable across various healthcare professions, who exercise a level of autonomy across four domains, referred to as the four pillars of practice (education, leadership, research and clinical practice). A national framework for ACP was established in 2017 to ensure consistency across the ACP role, however current ACP governance, education and support is yet to be evaluated. This study aimed to analyse data from a national survey of the ACP role to inform the development and improvement of policies relating to ACP in the National Health Service (NHS) in England. Design: A cross-sectional survey with free-text comments. Setting: The survey was distributed across primary and secondary levels of care to three distinct groups in England, including individual ACPs, NHS provider organisations and Trusts and primary care settings. Participants: A total of 4365 surveys were returned, from ACP staff (n=4013), NHS provider organisations and Trusts (n=166) and primary care organisations (n=186). Results: Considerable variation was found in role titles, scope of practice, job descriptions and educational backgrounds of ACPs. Differing approaches to governance were noted, which led to inconsistent ACP frameworks in some organisations. A further challenge highlighted included committing time to work across the four pillars of advanced practice, particularly the research pillar. ACPs called for improvements in supervision and continuing professional development alongside further support in navigating career pathways. Conclusions: A standardised approach may support ACP workforce development in England and enable ACPs to work across the four pillars of practice. Due to the wide uptake of ACP roles internationally, this study has relevance across professions for global healthcare workforce transformation